2023
DOI: 10.1186/s12905-022-02154-6
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin regulates the proliferation and apoptosis of ovary granulosa cells in polycystic ovary syndrome by modulating the PI3K/AKT/ERK signalling pathway

Abstract: Background The development of polycystic ovary syndrome (PCOS) is closely correlated with apoptosis and oxidative stress in ovarian granulosa cells. Kisspeptin plays an important role in reproductive organ function. This study aimed to explore the role of kisspeptin in PCOS and oxidative stress-triggered apoptosis of ovarian granular cells. Methods A PCOS rat model was established by injecting dehydroepiandrosterone (DHEA) and feeding the rats a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Treatment of CGCs with DHEAS shows altered 2-arachidonoylglycerol biosynthesis, 56 adrenaline and noradrenaline biosynthesis, alpha adrenergic receptor signaling, 34 TGF-beta signaling, 57 Toll receptor signaling, 58 VEGF signaling, 59 and PI3 kinase. 60 Based on these results and previous studies, we propose that MGCs and CGCs behave differently in the presence of DHEAS, possibly activating the pathogenesis of PCOS.…”
Section: Discussionsupporting
confidence: 69%
“…Treatment of CGCs with DHEAS shows altered 2-arachidonoylglycerol biosynthesis, 56 adrenaline and noradrenaline biosynthesis, alpha adrenergic receptor signaling, 34 TGF-beta signaling, 57 Toll receptor signaling, 58 VEGF signaling, 59 and PI3 kinase. 60 Based on these results and previous studies, we propose that MGCs and CGCs behave differently in the presence of DHEAS, possibly activating the pathogenesis of PCOS.…”
Section: Discussionsupporting
confidence: 69%
“…In fact, the reduction in testicular apoptosis appears to be via BCL-2, which showed gene expression almost three times higher in this group. Studies involving kisspeptin and apoptosis are inconsistent, but some have already demonstrated roles in attenuating apoptosis in neurons [62] and in granulosa cells in rat polycystic ovary model [37], which also showed an increase in BCL-2 [37,62], considered an antiapoptotic factor [39].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, kisspeptin, which control the hypothalamic release of gonadotropin-releasing hormone (GnRH) [29,30] and has local action in the testes [31,32], has been recognized for its antioxidant effects in models of ovarian and uterine, [33] testicular, [34], cardiac [35] and brain disease in mice [36]. In addition, in vitro overexpression of kisspeptin in human granulosa cells increased proliferation, inhibited apoptosis, suppressed ROS generation, reduced malondialdehyde (MDA) levels, and increased levels of antioxidant factors [37]. These effects observed in several studies justify the use of kisspeptin as a potent antioxidant factor in disease models.…”
Section: Introductionmentioning
confidence: 99%
“…| 5 of 10 aberrant inactivation of various signal transductions, such as Smad1/ 5/8, PI3K/Akt/mTOR, and NF-κB pathways seems to participate in PCOS-induced GC apoptosis. 68,[71][72][73] Furthermore, PCOS might drive GCs into death through apoptosis by downregulating Bcl-2 expression, as well as through ferroptosis by lowering the expression of glutathione peroxidase 4, SLC7A11, and Nrf2. 73 GCs make a substantial contribution to the acquisition of oocyte competence.…”
Section: Experimental Setting Species Pdcd4 Expression Cell Cycle Pro...mentioning
confidence: 99%
“…The main suppressor of p53, that is, MDM2, also showed downregulation, leading to a decrease in the ubiquitin‐dependent degradation of p53, and, consequently an increase in its cellular expression and transcriptional activity 70 . The aberrant inactivation of various signal transductions, such as Smad1/5/8, PI3K/Akt/mTOR, and NF‐κB pathways seems to participate in PCOS‐induced GC apoptosis 68,71–73 . Furthermore, PCOS might drive GCs into death through apoptosis by downregulating Bcl‐2 expression, as well as through ferroptosis by lowering the expression of glutathione peroxidase 4, SLC7A11, and Nrf2 73 …”
Section: Gc Apoptosis In the Pathogenesis Of Pcosmentioning
confidence: 99%